Knowledge and perceptions of medical interns about primary health care with a focus on family and community health - Rosales Anca, Angielina E. (2018)
Mr. Editor, this study is based on the documents of the Pan American Health Organization, referring to primary health care (PHC) in the Americas (1,2,3). Among the experiences and contributions of medical schools in PHC, Cuba and Brazil are the countries of Latin America that have demonstrated an initiative and a high governmental commitment in the development of it, emphasizing undergraduate training (3,4, 5). However, in most medical schools in the Americas, hospitals continue to be the only scenario for the practical training of students, leaving aside the family and community approach (6).